Adolescents’ social perceptions of academically high-performing students: a country and gender comparative study - Oh, Hyerim; Sutherland, Margaret; Stack, Niamh; del Mar Badia Martín, Maria; Blumen, Sheyla; Nguyen, Quoc Anh Thu; Wormald, Catherine; Maakrun, Julie; Ziegler, Albert (Compare, 2019)
One cohort that has not been given extended attention in the period during which transition takes place is academically high-performing students. This research study uniquely synthesises some of these key factors by investigating how students in mixed-ability, seventh-grade classrooms across Australia, Peru, Scotland, South Korea, Spain and Vietnam regard a hypothetical, academically able peer. The fictitious student’s intellectual ability, positive social traits and popularity varied across the six countries involved in this study, and were observed according to the gender of the perceiver. More specifically, the perceived popularity of a high-performing boy or girl was reported differently among the country groups. In Scotland, for example, the authors uncovered a potential risk to female social status arising from peer reactions to her academic achievement. Yet in Vietnam, female study participants maintained a positive perception of both hypothetical students, regardless of gender. The results of this study are discussed herein.
CRIS-Team Scopus Importer:2019-05-21
Keywords: High performer; intellectual ability; peer perception; popularity; positive social qualities